2007
DOI: 10.1080/13697130701297760
|View full text |Cite
|
Sign up to set email alerts
|

Menopause and aging, quality of life and sexuality

Abstract: In 19th century society, education and sexual activity were not considered appropriate for respectable women. There was a belief that neurasthenia, menstrual madness and hysteria were due to too much reading and listening to music. Certainly, women were too weak from their monthly loss to be worthy of education. Nymphomania, masturbation and moral insanity were generally believed by psychiatrists and gynecologists alike to be severe disorders which led to depression, coma, paralysis and death. There were many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
20

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 30 publications
1
23
0
20
Order By: Relevance
“…Studies have shown repeatedly that relationship factors (availability of sexual partner and quality of relationship) and psychological factors including mood, anxiety, and depression outweigh hormonal contribution to overall sexual function in menopausal-aged women. [16][17][18][19] During the MT, the symptom triad of disturbed sleep, depressed mood, and sexual problems may be more likely to co-occur in women with psychosocial risk factors. In our clinical population of midlife women aged 40-60 years seeking care from menopause specialists, 20% of women surveyed complained of the symptom triad of disturbed sleep, depressed mood, and sexual problems.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown repeatedly that relationship factors (availability of sexual partner and quality of relationship) and psychological factors including mood, anxiety, and depression outweigh hormonal contribution to overall sexual function in menopausal-aged women. [16][17][18][19] During the MT, the symptom triad of disturbed sleep, depressed mood, and sexual problems may be more likely to co-occur in women with psychosocial risk factors. In our clinical population of midlife women aged 40-60 years seeking care from menopause specialists, 20% of women surveyed complained of the symptom triad of disturbed sleep, depressed mood, and sexual problems.…”
Section: Introductionmentioning
confidence: 99%
“…Внешним проявлением такого дезадаптивно-го ответа становятся вазомоторные (приливы жара, ночная потливость) и психосоматиче-ские (раздражительность, вялость, утомляе-мость, депрессия, головные боли, нарушение памяти, расстройства сна, суставные боли, сердцебиение, истерические припадки, сни-жение либидо и др.) симптомы, снижающие качество жизни и вынуждающие обращаться за медицинской помощью [1][2][3].…”
Section: Introductionunclassified
“…Внешним проявлением такого дезадаптивно-го ответа становятся вазомоторные (приливы жара, ночная потливость) и психосоматиче-ские (раздражительность, вялость, утомляе-мость, депрессия, головные боли, нарушение памяти, расстройства сна, суставные боли, сердцебиение, истерические припадки, сни-жение либидо и др.) симптомы, снижающие качество жизни и вынуждающие обращаться за медицинской помощью [1][2][3].Развитие вазомоторной и психосоматиче-ской симптоматики опережает возникнове-ние обменных и урогенитальных менопау-зальных нарушений [4]. Это отмечают 35-80% женщин, находящихся на стадиях менопау-зального перехода и постменопаузы, а от 50 до 70% пациенток обращаются за медицин-ской помощью по поводу климактерических нарушений.…”
unclassified
“…However, with improvement in general living conditions women are now more concerned about sexual wellbeing in later life [10].…”
Section: Health Problems In the Post-reproductive Agementioning
confidence: 99%